Effect of conjoint use of bioactive phosphocompost and chemical fertilizers on plant growth and soil properties under pea (Pisum sativum) cropping - THAKUR, DEEPSHIKHA; KAUSHAL, RAJESH; SHYAM, VINEET (The Indian Journal of Agricultural Sciences, 2018)
The field experiment was conducted to study the effect of conjoint use of bioactive phosphocompost and recommended dose of chemical fertilizers on various plant, soil and microbiological parameters under pea (Pisum sativum L.) crop. The bioactive phosphocompost (0.98%, 2.24%, 0.81% N, P, K respectively), was used in six different combinations with the chemical fertilizers. Out of the six treatment combinations, treatment T3 (conjoint use of 75% recommended dose of chemical fertilizers and 25% phosphocompost) proved to be significantly superior in increasing the various plant parameters such as shoot length (76.25 cm), root length (22.25 cm), total plant biomass (40.78q/ha), green pod yield (219 q/ha) etc., over control. The significantly higher content of N (4.54%), P (0.55%) and K (2.39%) was also recorded in T3 treatment. Although, significantly higher organic matter (1.32%), CEC (44.37 c mol (p+)/kg), available P (143.33 kg/h) and soil enzyme activities were recorded in T6 treatment (100% phosphocompost). Various microbiological properties like microbial biomass, microbial activity, total microbial count, P solubilizer count, Rhizobium count and siderophore producers were also recorded highest in T6 treatment. On the basis of results, it can be concluded that the conjoint use of 75 % recommended dose of chemical fertilizers and 25% phosphocompost, increased the yield of pea by 58% and is thus recommended to be used for higher yield, improved nutrient status, improved physico-chemical and microbiological properties of soil, directing towards sustainable farming.